2014
DOI: 10.1002/mrm.25403
|View full text |Cite
|
Sign up to set email alerts
|

A home‐built digital optical MRI console using high‐speed serial links

Abstract: A homemade digital optical MRI console with high-speed serial interconnection has been developed to better serve imaging research and clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…These drawbacks limit prototype production by a wider community and hinder new developments. To overcome these limitations, several home‐spun designs have emerged during the last decade, mainly based on field programmable gate arrays (FPGAs) 29–36 . The MaRCoS initiative is an attempt to centralize these efforts to become a versatile, low‐cost, and open‐source solution fostering the development of present and future LF‐MRI technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drawbacks limit prototype production by a wider community and hinder new developments. To overcome these limitations, several home‐spun designs have emerged during the last decade, mainly based on field programmable gate arrays (FPGAs) 29–36 . The MaRCoS initiative is an attempt to centralize these efforts to become a versatile, low‐cost, and open‐source solution fostering the development of present and future LF‐MRI technologies.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, several home‐spun designs have emerged during the last decade, mainly based on field programmable gate arrays (FPGAs). 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 The MaRCoS initiative is an attempt to centralize these efforts to become a versatile, low‐cost, and open‐source solution fostering the development of present and future LF‐MRI technologies. The MaRCoS community is therefore open and has the ambition of expanding the range of tools this platform provides as new needs arise.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was applied for single receive elements at 0.18 and 4.7 T [36,37]. Multichannel scalable solutions in combination with optical fibers were proposed for in-field receivers with one ADC per coil element at 1.5 and 3 T [18,19], and four-channel ADCs for MRI up to 2.4 T with an eight-channel coil [38,39]. Recent research also demonstrated a digital RF front end adaptable for 16 channels and useable from 1.5 to 11.7 T [20,22].…”
Section: Signal Digitizationmentioning
confidence: 99%
“…Among the projects opened to the community [2], [18]- [24], the Open-source Console for Real-time Acquistion (OCRA [21]) is notable for its flexibility, inexpensive off-the-shelf components, community focus, and real-time capabilities. The MAgnetic Resonance COntrol System (MaRCoS [3]) uses the same versatile hardware, however its software, firmware and FPGA firmware have been replaced to go beyond the limitations of OCRA.…”
Section: Introductionmentioning
confidence: 99%